Cultural landscape function of informal urban settlement in East Nusa Tenggara - Roosna Maryani Octaviana Adjam; Imam Buchori; Wakhidah Kurniawati (Jurnal Teknosains, 2023)
The theme of cultural landscape function becomes very important along with the awareness to create a balance of ecological and social landscape functions in urban areas. Urban settlement strongly influences cultural function, both as a form of landscape and demographic characteristics. This paper aims to examine the existence of several important social values in urban settlement landscapes and the role of landscape features in influencing social values aspects of informal residents such as social cohesion, recreation, sense of place, spiritualism, cultivation, and business activities. The research method used is a mixed quantitative and qualitative method by using observations, questionnaires, and interviews for data collection based on a sociological approach with community members. Questionnaire data were collected for further analysis in which the Spearman coefficient was used to examine the relationship between social values and landscape features. The results revealed that residents in Airmata and Manutapen have different percentages of social values in terms of their landscape features, and it can also be seen that the values of social cohesion, sense of place, and local business present a stronger relationship to landscape functions. These results show the importance of social values in informal societies as a potential approach to achieving sustainable landscape management.